2022
DOI: 10.3390/s22093195
|View full text |Cite
|
Sign up to set email alerts
|

Passive Attenuation of Mechanical Vibrations with a Superelastic SMA Bending Springs: An Experimental Investigation

Abstract: This work presents an experimental study related to the mechanical performance of a special design spring fabricated with a superelastic shape memory alloy (SMA-SE). For the experimental testing, the spring was coupled in a rotor machine, aiming to attenuate the mechanical vibration when the system went through a natural frequency without any external power source. It was verified that the reduction in instabilities stemmed from the better distribution of vibration force in the proposed device, as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Reference [ 19 ] reviewed SMAs in robotics applications in terms of control aspects. Reference [ 20 ] presented an experimental investigation of mechanical vibration attenuation with superelastic SMA bending springs. Reference [ 21 ] designed SMA spring-based actuators with a combined micro-macro mechanics analytical approach and presented its experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [ 19 ] reviewed SMAs in robotics applications in terms of control aspects. Reference [ 20 ] presented an experimental investigation of mechanical vibration attenuation with superelastic SMA bending springs. Reference [ 21 ] designed SMA spring-based actuators with a combined micro-macro mechanics analytical approach and presented its experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis showed that the first model was more efficient due to its higher dissipation capacity. The same device was used by Senko et al [19] maintaining a constant pre-load throughout the test, reducing involved instabilities, and increasing the dissipation capacity without the use of an external source of energy.…”
Section: Introductionmentioning
confidence: 99%